Bacteriological study of the cerebrospinal fluid(CSF) of children with meningitis in Baghdad - Ahmed .K.H.Al Hassan; Zaid M. M. Al Muhdaw; Nada A. Al Hasso (Tikrit Journal of Pure Science, 2023)
The study included 92 samples of CSF taken from children aged 1day to 10 years with meningitis. The study was conducted in the hospitals of  Medical City in Baghdad. The samples were obtained by a specialized staff. Conventional direct Gram stain and culture tests were performed. The study sample were categorized into three group a (1day to 2 years), (2 to 6 years) and (6 to 10 years).